2013
DOI: 10.1371/journal.pone.0059222
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Secretion of Human Proinsulin-B10 from Mouse Salivary Glands: Implications for the Treatment of Type I Diabetes Mellitus

Abstract: Adenovirus (Ad) mediated expression of therapeutic proteins from salivary glands can result in the delivery of biologically active proteins into the circulation where they impart their physiological function. In recent years, Ad vector delivery to salivary glands (SGs) has emerged as a viable option for gene therapy. Here, we engineered a variant of human proinsulin (hProinsulin-B10) into an Ad vector and demonstrated its ability to transduce cell lines, and express a bioactive protein that induces the phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…However, once expressed in SGs, the issue of where WT hGH is secreted is a real problem – in this case predominantly through the RSP into the saliva where it would not be therapeutically useful (He et al , ). Hence, efforts to identify and generate functional mutants of hGH that are synthesized and can be trafficked and secreted from polarized cells through either the non‐regulated or CSP could yield promising proteins for their use in treating IGHD after expressing them in the parenchymal cells of the salivary gland with subsequent secretion into the circulation as recently done for GLP‐1, proinsulin, and erythropoietin (Monami et al , ; Rocha et al , ; Rowzee et al , ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, once expressed in SGs, the issue of where WT hGH is secreted is a real problem – in this case predominantly through the RSP into the saliva where it would not be therapeutically useful (He et al , ). Hence, efforts to identify and generate functional mutants of hGH that are synthesized and can be trafficked and secreted from polarized cells through either the non‐regulated or CSP could yield promising proteins for their use in treating IGHD after expressing them in the parenchymal cells of the salivary gland with subsequent secretion into the circulation as recently done for GLP‐1, proinsulin, and erythropoietin (Monami et al , ; Rocha et al , ; Rowzee et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Salivary glands (SGs) are promising target organs for gene therapeutics (Kagami et al , ; O'Connell et al , ; Baum et al , , ; Wang et al , ; Perez et al , ; Zheng et al , ; Monami et al , ; Rocha et al , ; Rowzee et al , ). They can secrete proteins in large amounts apically to the saliva (O'Connell et al , ; Baum et al , ) or basolaterally to the circulation (Kagami et al , ; Wang et al , ; Perez et al , ), the latter of which can be used for systemic delivery of therapeutic proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Within the last six or so months, two papers have been published (Ma, Fan, Gao, Wang, & Shan, ; Wang et al., ) using gene transfer to salivary glands to treat preclinical animal models of serious systemic diseases. These are not the first reports of such a possibility, for example, my colleagues and I reported that transferring the cDNA of a modified human glucagon‐like peptide‐1 to salivary glands can be used to treat a mouse model of type 2 diabetes (Voutetakis et al., ), while transferring the cDNA encoding a variant of human proinsulin‐B10 can be used to treat a mouse model of type 1 diabetes (Rowzee et al., ).…”
mentioning
confidence: 99%
“…These studies have been conducted only in animals, although in many species (mouse, rat, miniature pig, and macaques), but have not yet reached the clinic. There have been multiple endocrine applications suggested, including proposed treatments [gene or cDNA indicated if not obvious] for growth hormone deficiency (Hoque et al , ), chronic anemia (erythropoietin; Voutetakis et al , ), Fabry disease ( α ‐galactosidase; Passineau et al , ), α ‐1‐antitrypsin deficiency (Perez et al , ), and diabetes (type 1, proinsulin B10, Rowzee et al , ; type 2, glucagon‐like peptide 1, Voutetakis et al , ). There have been fewer examples for exocrine use, azole‐resistant candidiasis (histatin 3; O'Connell et al , ) and radiation‐induced mucositis (keratinocyte growth factor; Zheng et al , ).…”
mentioning
confidence: 99%